Effect of Growth Temperature on Zno Nanostructures Thin Film Fabricated using Tcvd Method - A.Rahman, R.; A.Karim, S.; B.Rosli, A.; A.Zulkifli, M.; Zulkifli, Z.; Kamaruzzaman, D. (International Journal of Engineering and Technology, 2018)
The objective of this study is to explore the effects of ZnO growth temperature on the formation of the nanostructures. ZnO nanostructures was grow on the ITO coated glass substrate with the application of double furnace system of thermal chemical vapor deposition (TCVD) method. During growing process, the growth temperatures were varied in 50 ºC interval temperature (500 ºC-650 ºC) while the other parameters such growth time, precursor temperature, annealing time and temperature were remain constant. After the growing and annealing process were completed, all of the films were characterized physically, electrically and also optically using field emission scanning electron microscope (FESEM), surface profiler, I-V measurement and also ultraviolet visible (UV-Vis). FESEM results reveal that all growth temperature shows a formation of nanotetrapod ZnO film. The highest of growth temperature exhibited long and thin leg of nanotetrapod, with the lowest thickness value of 14.90 nm. As the growth temperatures increase, ZnO nanostructures change with the decreasing thickness value. Other than that, I-V results indicate that resistivity of the films increase when the growth temperatures were raised, so as the optical energy band gap values. Highest growth temperature shows highest value of resistivity and optical band gap with the value of 32.49 x 103 Ω.cm and 3.32 eV. Overall, the results obtained proved that the growth temperature affect the characteristics of the film, where the morphology, thickness, I-V, transmittance, absorbance and optical band gap changes with the increasing growth temperatures.